The preferences of Trieste inhabitants for the re-use of the old port: a conjoint choice experiment - Jérôme Massiani; Paolo Rosato (Fondazione Eni Enrico Mattei (FEEM), 2008)
In many developed countries, abandoned (derelict or underused) industrial areas often occupy important parts of the cities. This raises issues about the possibilities of reusing these areas as well as on the conservation of industrial heritage they often entail. Conjoint Analysis (CA) can shed light on these issues as it can elicit the preferences of inhabitants for different scenarios of reuse. So far, only a limited number of applications of CA have been made on this topic. In this article, we present the results of a CA experiment on the reuse of a large, mainly abandoned, port area in Trieste (Italy) featuring buildings with some historical and industrial heritage value. Three hundred computer assisted interviews have been made on a representative sample of Trieste inhabitants, eliciting their preferences for different reuse hypotheses and building conservation scenarios. The survey explores two original topics: the impact of the time horizon of the payment (single or decennial special purpose tax) and the consideration of various mixes of future uses. The collected data have been processed using latent class and mixed logit models to explore heterogeneity among interviewees' preferences. Our findings show that, while preferences clearly emerge in favor of tourism and leisure oriented uses, preferences in terms of conservation and the impact of cost are much more difficult to measure. This difficulty persists even when specified or non specified heterogeneity is taken into account, although Mixed Logit estimate provides more convincing results.
Keywords: H43; R52; R10; 330; Land Use; Port; Trieste; Conjoint Analysis